Synthesis of holmium orthoferrite nanoparticles by the co-precipitation method at high temperature - Tien, Nguyen Anh; Hien, Truong Chi; Vương, Bùi Xuân (Metallurgical and Materials Engineering, 2021)
Holmium orthoferrite HoFeO3 nanoparticles were synthesized by a simple co-precipitation method via the hydrolysis of Ho (III) and Fe (III) cations in boiling water with 5% aqueous ammonia solution. After annealing the precipitate at 750 and 850 °C for 1 hour, the single-phase HoFeO3 product formed with particle size < 50 nm. The synthesized nanopowders are paramagnetic materials with remanent magnetization Mr < 0.01 emu ·g-1, the coercive force Hc = 20÷21 Oe, and magnetization Ms ~ 2.73 emu ·g-1 at 300 K in a maximum field of 16,000 Oe.